Fibromatosis, a benign breast disease mimicking carcinoma. A case report - Ashoor, Arwa (Int J Surg Case Rep, 2017)
INTRODUCTION: Fibromatosis is an uncommon breast lesion that can mimic breast carcinoma in its clinical presentation. CASE SUMMARY: We present a clinical case in which a diagnosis and treatment dilemma existed, in terms of ultrasound findings that were not clear and suspicious, as well as results of Fine needle aspiration cytology. Our findings are compared with previous published cases. Also, literature review regarding fibromatosis presentation and diagnosis has been discussed, as well as treatment options. CONCLUSION: Management of breast fibromatosis remains controversial because of the low incidence and further efforts needed to establish evidence-based treatment guidelines.